ANALISIS KESTABILAN MODEL PREDATOR PREY DENGAN TINGKATAN USIA PADA DUA PREY DAN DUA PREDATOR DENGAN FUNGSI RESPON MONOD HALDANE DAN KANIBALISME - Robiatul Witari Wilda; Dita Monita; Febrianto Afli; Ahmad Muammar Kadafi (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
This paper discusses a predator-prey stage structure model for two predators and two preys with Monod Haldane and cannibalism response functions that describe the interactions between populations of young prey, adult prey, young predator, and adult predator. In this model it is assumed that only adult predators are capable of attacking to consume young predators, only adult prey are capable of reproduction, there is a Monod-Haldane effect describing the phenomenon of group defense where predation is reduced, or even prevented altogether, because the ability increases from prey for further defense or camouflage when their numbers are large enough. Dynamic analysis is carried out by determining the equilibrium point and its existence conditions and analyzing the local stability of the equilibrium point. The predator-prey model has three equilibrium points, namely the trivial equilibrium point, the prey free equilibrium point and an interior point that exists under certain conditions. The equilibrium points is locally asymptotically stable under certain conditions. The results of the numerical simulations show suitability with the results of dynamic analysis.